Molecular mobility in rubbers - Allen Geoffrey (Journal of Natural Rubber Research, 1986)
Neutron beams be obtained in pulsed beams of virtually monchromatic character at wavelengths of about 5 A. The momentum associated with the beam is high and the energy low. Thus neutrons are ideal for studying the diffulsional motions of liquids in scattering experiments. In the past ten years, neutron scattering has been used to determine the average dimensions of individual chains in bulk rubbers and plastics, to study the dynamics of polymer chains in raw rubbers and melts and cross-linked networks and to measure the rotation of side groups. Results show that the Rouse model of molecular chain dynamics is more appropriate than the Zimm model for rubber. In networks, the sections of chain between cross-links from essentially the same chain motion as in the raw rubber, but the junction joints move more slowly. The energy barrier to internal rotation of the methyl side groups in polypropylene oxide is found to be approximately 15 kJ mol-1 in line with the expected value.
Keywords: Molecular mobility; Rubber